Malignant pleural mesothelioma: New hope in the horizon with novel therapeutic strategies. Issue 1 (January 2015) - Remon, J.; Reguart, N.; Corral, J.; Lianes, P.
Highlights Malignant pleural mesothelioma (MPM) incidence has increased and it is not expected to drop until 2015 and 2030. Germline mutations could help identifying individuals at high risk of MPM who could be targeted for early intervention. Molecular landscape and identification of deregulated pathways may help to achieve a customized therapy in MPM. FAK inhibitors, antiangiogenic therapies, NGR-hTNF are promising new therapies in MPM. Immunotherapy offers a promising activity in MPM.